2015
DOI: 10.1039/c5an00641d
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of boron- and nitride-doped MoS2 nanosheets as fluorescent probes for the ultrafast, sensitive, and label-free detection of Hg2+

Abstract: Bulk MoS2, a prototypical transition metal chalcogenide material, is an indirect band gap semiconductor with negligible photoluminescence. In this study, we have developed, for the first time, a simple and low-cost synthetic strategy to prepare boron- and nitrogen-doped MoS2 (B,N-MoS2) nanosheets. Through boron and nitrogen doping, the band gap of MoS2 increases from 1.20 eV to 1.61 eV, and the obtained B,N-MoS2 nanosheets exhibit an enhanced fluorescence. The B,N-MoS2 nanosheets can be used as a green and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…11,15,24 Moreover, the very sharp peak of high intensity and strong peak of XRD spectra further confirm a well-stacked crystalline structure. 9,11,20,24 Apparently, MoS 2 @Fe 3 O 4 NPs exhibited peaks at 2θ = 29.2, 30.3, 32.9, 33.7, 35.7, 39.8, 44.4, 50.0, 57.2, and 58.5° (Figure 2D). Two new weak diffraction peaks emerge from the low-angle region, where 32° corresponds to the (100) plane of the pristine 2H-MoS 2 , indicating the formation of MoS 2 @Fe 3 O 4 NPs.…”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11,15,24 Moreover, the very sharp peak of high intensity and strong peak of XRD spectra further confirm a well-stacked crystalline structure. 9,11,20,24 Apparently, MoS 2 @Fe 3 O 4 NPs exhibited peaks at 2θ = 29.2, 30.3, 32.9, 33.7, 35.7, 39.8, 44.4, 50.0, 57.2, and 58.5° (Figure 2D). Two new weak diffraction peaks emerge from the low-angle region, where 32° corresponds to the (100) plane of the pristine 2H-MoS 2 , indicating the formation of MoS 2 @Fe 3 O 4 NPs.…”
Section: Results and Discussionmentioning
confidence: 98%
“…19,23 For the bulk MoS 2 sample, two characteristic Raman peaks are attributed to 390 and 416 cm –1 , which correspond to the A 1g and 1 E 2g vibration modes (Figure 1B). 11,15,20 Related peak frequency difference is Δ k = 26 cm –1 . However, as-synthesized MoS 2 @Fe 3 O 4 NP peaks were slightly shifted to 392 and 417 cm –1 , which correspond to the A 1g and 1 E 2g vibration modes (Figure 1C).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Chemical doping in 2D nanomaterials could change their band gap and thus affect their optical properties . Bearing this in mind, Feng et al developed a sonication method to prepare boron‐ and nitrogen‐co‐doped MoS 2 (B,N–MoS 2 ) nanosheets . Through the co‐doping of boron and nitrogen, they found that the band gap of MoS 2 nanosheets increased from 1.20 to 1.61 eV and the synthesized B,N–MoS 2 nanosheets possessed an enhanced fluorescence.…”
Section: Tmd Nanosheets and Their Composite‐based Optical Sensorsmentioning
confidence: 99%
“…In the past decades, the modification of MoS 2 nanocrystals has been widely investigated . For example, nitrogen‐doped MoS 2 nanocrystals (NDMN) have found extensive application in electrical and optical fields, due to their better optoelectronic properties than pristine MoS 2 . However, to the best of the authors' knowledge, no literature has reported on the application of NDMN towards azo dyes removal.…”
Section: Introductionmentioning
confidence: 99%